The Spousal Support And Knowledge Influence Exclusive Breastfeeding - Elvi Destariyani; Suci Sholihat; Vina Ananda (International Journal of Health Sciences, 2025)
Exclusive breastfeeding is essential for the health of mothers and children; however, its coverage remains low, with only 44% of infants aged 0-6 months worldwide receiving exclusive breastfeeding. This low coverage can lead to health issues for both infants and mothers. Objective: This study aims to analyze the relationship between maternal knowledge and spousal support regarding exclusive breastfeeding in the working area of Puskesmas Kandang, Bengkulu City, in 2025. Methods: The research design used is analytical with a cross-sectional approach. The sample consists of 106 breastfeeding mothers with infants aged 7-12 months. Data were analyzed univariately and bivariately using the chi-square test. Results:The analysis results indicate a significant relationship between maternal knowledge (p = 0.000) and spousal support (p = 0.001) with exclusive breastfeeding at Puskesmas Kandang. Conclusion: This study is expected to contribute to academic development and Puskesmas, as well as encourage the enhancement of educational programs regarding the benefits of exclusive breastfeeding, involving husbands as primary supporters to increase exclusive breastfeeding coverage and support the health of mothers and infants.